Britain and its mandate over Palestine : legal chicanery on a world stage / John Quigley. - Quigley, John B. (Anthem Press, 2023)
Analysis of Britain's role in Palestine has proceeded on the assumption that Britain was lawfully in control of the territory. Analysts differ on whether what it did was proper, but they agree that Britain had a lawful mandate and that through the League of Nations, and that the international community advocated for Jewish territorial rights in Palestine. This analysis, though widely shared, is incorrect. Britain had no territorial rights itself to govern Palestine. It was there by dint of force of arms. The mandate it had over Palestine was initiated unilaterally. The mandate was not given to Britain by the League of Nations. The League of Nations had no authority over Palestine and, in particular, nothing it could give to Britain. The document that Britain composed for the governance of Palestine was never approved by the League of Nations.